Criminal proceedings for offenses against the environment - Bugarski, Tatjana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
Ecological crime is not recognized as a serious risk for any society in the professional and the general public, despite all the obvious indicators and manifestations of its features that make it a serious and severe form of crime, hence not enough attention is paid to it. In this paper, author deals with one aspect of the problem of ecological crimes, forms of this type of crime and specific issues in relation to criminal proceedings for these offenses in the Republic of Serbia. Special attention is paid to problems of victim in these criminal proceedings.